A method for grafting quaternary ammonium cations and phenolic ammonium zwitterions on glass surface

By grafting quaternary ammonium cations and phenolic ammonium zwitteriones on the glass surface, the problems of glass surface pollution and light transmittance are solved, and super hydrophilic and antibacterial effects are achieved, and self-cleaning properties are provided.

CN116395988BActive Publication Date: 2025-03-25SI CHUAN JING LANG KE JI JI TUAN YOU XIAN GONG SI

Patent Information

Application Number
CN202310116725.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-15
Publication Date
2025-03-25
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

Existing glass products are prone to surface pollution and reduced light transmittance during use, and it is difficult to effectively prevent the adhesion and growth of dust, suspended organic matter or microorganisms.

Method used

By performing the ring-opening reaction of epoxypropane and amino group on the glass surface, then reacting with quaternary ammonium saltization of 5-chloromethyl salicylic aldehyde, and then reacting with the secondary quaternary ammonium saltization of tertiary amine, functional modification of grafted quaternary ammonium cations and phenolic ammonium zwitterionic ions on the glass surface.

Benefits of technology

This method realizes super hydrophilicity of the glass surface, enhances antibacterial ability, can effectively prevent the adhesion and growth of pollutants, maintain the light transmittance of the glass, and has self-cleaning characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004078822180000021
    Figure BDA0004078822180000021
  • Figure BDA0004078822180000031
    Figure BDA0004078822180000031
  • Figure BDA0004078822180000051
    Figure BDA0004078822180000051
Patent Text Reader

Abstract

The invention provides a method for grafting quaternary ammonium cations and phenolic ammonium zwitterions on a glass surface, and particularly relates to a method for grafting quaternary ammonium cations and phenolic ammonium zwitterions on the glass surface through a ring-opening reaction between ammonium epichlorohydrin and amino groups on the glass surface, followed by a quaternary ammonium salting reaction with 5-chloromethyl salicylaldehyde, and then a secondary quaternary ammonium salting reaction with a tertiary amine, so as to achieve the modification of grafting quaternary ammonium cations and phenolic ammonium zwitterions on the glass surface. The method provided by the invention achieves the super-hydrophilic property of the glass surface, and the technology is simple and easy to implement, the raw materials used are widely available, the price is low, the reaction efficiency of each preparation step is high, and there is no mutual influence before and after the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for functionalizing a glass surface, in particular to a method for grafting quaternary ammonium cations and phenolic ammonium zwitterions on the glass surface. The method comprises the following steps: a ring-opening reaction between epichlorohydrin and amino groups on the glass surface, a quaternary ammonium salting reaction with 5-chloromethyl salicylaldehyde, and a secondary quaternary ammonium salting reaction with a tertiary amine, so as to achieve functional modification of grafting quaternary ammonium cations and phenolic ammonium zwitterions on the glass surface. The method belongs to the technical field of glass surface. Technical Background

[0002] Glass is an isotropic amorphous inorganic material with high light transmittance, high hardness, high pressure resistance, wear resistance and corrosion resistance. In view of its good processability, it has been widely made into glass products for daily use, vehicle windshields, medical glass products, glass curtain walls, glass greenhouses, photovoltaic glass, glass optical windows for underwater equipment and instruments, etc. However, these glass products will inevitably adsorb dust, suspended organic matter or microorganisms in the environment on the surface when in operation, or fog in cold air, etc., which will cause glass surface pollution and reduced light transmittance, or even "blindness". For this reason, people have found that the use of vapor deposition technology, photolithography technology or nanotechnology to deposit a nanoparticle layer on the glass surface, using the ultra-high surface energy of the nanoparticles to create super-hydrophilicity on the glass surface, forming a super-hydrophilic film on the glass surface under normal conditions, catalyzing the generation of superoxide radicals and hydroxyl radicals under sunlight irradiation, these free radicals can oxidize and degrade organic matter or microorganisms attached to the glass surface, causing them to decompose or die, and then be washed away by rainwater, thus achieving self-cleaning of the glass surface.

[0003] At present, people have clearly known that self-cleaning glass can be made by greatly improving the surface hydrophilicity of glass. For example, CN201210442595.7, CN201410321560.7, CN201410145198.2, CN201410551397.3, CN201110155872.1, and CN202210463398.7 all use silane coupling agents carrying -C=C, -NH2, -SH, -NCO or epoxy groups to form new chemical active centers on the glass surface through condensation reactions. The active center can be grafted and copolymerized to link polyethylene glycol, polyacrylic acid, polyacrylamide, quaternary ammonium carboxylic acid inner salt, quaternary ammonium phosphate inner salt or quaternary ammonium sulfonic acid inner salt, etc. These hydrophilic substances form a hydration layer on the glass surface, which can isolate and prevent dust or microorganisms in the air from contacting or adhering to the glass surface; or some antibacterial agents such as capsaicin, chloramine, quaternary ammonium salts can be introduced by grafting polymerization on the glass surface to kill or inhibit the reproduction and growth of microorganisms on the glass surface, and use natural rainwater to wash away all dirt on the glass surface.

[0004] The bonding of quaternary ammonium salts to the glass surface is a kind of glass surface functionalization. The moisture absorption and hygroscopicity of some quaternary ammonium salts can not only greatly improve the hydrophilicity of the glass surface under normal conditions, but also be an excellent non-sustained-release antibacterial agent with the characteristics of stable properties, designable chemical structure, simple preparation method, low irritation to the human body and broad antibacterial spectrum. Therefore, it is of great significance to bond quaternary ammonium salts to the glass surface by a simple method. Summary of the invention

[0005] The present invention provides a method for grafting quaternary ammonium cations and phenolic ammonium zwitterions onto a glass surface. The technical solution of the present invention is implemented by a preparation process as shown in the following reaction formula:

[0006]

[0007] Wherein R1, R2 and R3 in the reaction formula are selected from substituted or unsubstituted C1-C 18 Hydrocarbyl, wherein R in the general formula (2) is selected from -F, -Cl, -Br, -OH, (CH3)2N-, -COOH, -SO3H or substituted or unsubstituted C1-C 18 One or more hydrocarbon groups.

[0008] The specific method for grafting quaternary ammonium cations and phenolic ammonium zwitterions on the glass surface comprises the following steps:

[0009] Step 1: Add a mixed solution of 98% concentrated sulfuric acid and 30% hydrogen peroxide on one side of a cleaned and dried glass substrate, control the temperature at 20-120°C, and control the time for 0.5-50 hours. Then take out the glass substrate, clean the surface of the glass sheet with deionized water, and then vacuum dry it at 60-90°C to obtain a surface hydroxylated glass sheet.

[0010] The volume ratio of concentrated sulfuric acid to hydrogen peroxide in the mixed solution is 9:1 to 7:3, and the amount of the mixed solution is 2 to 200% of the mass of the glass substrate.

[0011] Step 2: Add aminosilane coupling agent solution to one side of the hydroxylated glass sheet obtained in step 1, put it in an oven at 30-130° C., control the time for 0.5-20 hours, take it out and cool it to obtain a glass sheet with surface amino.

[0012] The mass ratio of aminosilane coupling agent: ethanol: water in the aminosilane coupling agent solution is 1-5:50-98:5-45, and the amount of the aminosilane coupling agent solution is 2-200% of the mass of the glass substrate.

[0013] The aminosilane coupling agent refers to one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-ethyl-3-aminopropyltrimethoxysilane, N-ethyl-3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane and 3-aminopropyldiethoxymethylsilane.

[0014] Step 3: Slowly add epichlorohydrin to the surface of the amino-treated glass sheet, place it in a reactor, control the temperature at 20 to 60° C., control the reaction time at 0.5 to 20 hours, and then use N2 to blow away the unreacted epichlorohydrin to obtain a glass sheet with a surface tertiary amino group.

[0015] The amount of epichlorohydrin used is 5-500% of the mass of the glass substrate.

[0016] Step 4: Add 5-chloromethyl salicylaldehyde solution to the surface of the tertiary aminated glass sheet obtained in step 3, put it into a reactor at 0-60° C., control the reaction time to 0.5-50 hours, then take it out and use acetone to wash and remove the unreacted 5-chloromethyl salicylaldehyde on the glass sheet, and after drying, obtain a surface quaternized glass sheet.

[0017] The mass ratio of 5-chloromethyl salicylaldehyde to organic solvent in the 5-chloromethyl salicylaldehyde solution is 0.01-0.5:1, and the amount of the 5-chloromethyl salicylaldehyde solution is 2-200% of the mass of the glass substrate.

[0018] The organic solvent refers to one or more of acetone, butanone, cyclohexanone, methyl acetate, ethyl acetate, chloroform, 1,2-dichloroethane, carbon tetrachloride, tetrahydrofuran, 1,4-dioxane, decahydronaphthalene, toluene, chlorobenzene, dimethyl sulfoxide or N,N-dimethylacetamide.

[0019] Step 5: Add tertiary amine solution to the surface of the quaternized glass sheet obtained in step 4, put it into a reactor at 20-90° C., control the reaction time for 0.5-50 hours, wash the glass surface with a solvent, recover the unreacted tertiary amine, and dry it to obtain glass with quaternary ammonium cations and phenol ammonium zwitterions grafted on the surface.

[0020] The mass ratio of tertiary amine to solvent in the tertiary amine solution is 0.5:0-5, and the amount of the tertiary amine solution is 5-500% of the mass of the glass substrate.

[0021] The tertiary amine has a structure shown in general formula (1) or general formula (2):

[0022]

[0023] Wherein R1, R2 and R3 in the general formula (1) are selected from substituted or substituted C1-C 18 Hydrocarbyl, wherein R in the general formula (2) is selected from -F, -Cl, -Br, -OH, (CH3)2N-, -COOH, -SO3H or substituted or unsubstituted C1-C 18 One or more hydrocarbon groups.

[0024] The solvent refers to one or more of water, methanol, ethanol, acetone, butanone, cyclohexanone, methyl acetate, ethyl acetate, chloroform, 1,2-dichloroethane, carbon tetrachloride, tetrahydrofuran, 1,4-dioxane, decahydronaphthalene, toluene, chlorobenzene, dimethyl sulfoxide or N,N-dimethylacetamide.

[0025] The beneficial effects of the method for grafting quaternary ammonium cations and phenol ammonium zwitterions on the glass surface provided by the present invention are:

[0026] ① The method for grafting quaternary ammonium cations and phenolic ammonium zwitterions on the glass surface provided by the present invention is simple in technology and easy to implement, the raw materials used are widely available and inexpensive, each preparation step has high reaction efficiency, and there is no mutual influence before and after the preparation process.

[0027] ② The functionalized layers after the quaternary ammonium cations and phenolic ammonium zwitterions are grafted onto the glass surface of the present invention are all monolayers, showing a lattice distribution with high uniformity. Therefore, the light transmittance of the modified glass will not be affected by the grafting of quaternary ammonium cations and phenolic ammonium zwitterions onto its surface. DETAILED DESCRIPTION

[0028] In order to further understand the present invention, the present invention is specifically described by way of examples, the purpose of which is to better understand the content of the present invention. Therefore, the method of grafting quaternary ammonium cations and phenol ammonium zwitterions on the glass surface not listed in the examples should not be regarded as limiting the scope of protection of the present invention.

[0029] Example 1 Preparation of glass sheet (1-a) with surface grafted quaternary ammonium cations and ammonium phenol zwitterions

[0030] Step 1: Clean and dry a 2.5*7.6*0.15cm glass substrate (glass slide, Jiangsu Feizhou Glass Plastic Co., Ltd.), prepare 5 grams of a mixed solution of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3, then add it to the glass slide, treat it at 60-70°C for 2 hours, rinse it with deionized water until it is weakly acidic, and vacuum dry it at 60°C to obtain a surface hydroxylated glass slide (1-a).

[0031] Step 2: prepare 8 g of 3-aminopropyltrimethoxysilane solution according to the mass ratio of 3-aminopropyltrimethoxysilane: ethanol: water of 2:90:8, add it to the surface of the hydroxylated glass sheet (1-a) obtained in step 1, put it in an oven at 80-90° C., take it out after 1 hour and cool it to obtain the surface-amino-treated glass sheet (1-a).

[0032] Step 3: Place the amino-treated glass sheet (1-a) obtained in step 2 into a reactor at 45-55° C., slowly add 4.5 g of epichlorohydrin onto its surface, react for 12 hours, take it out, and use N2 to blow dry the glass surface to obtain a surface-tertiary-amined glass sheet (1-a).

[0033] Step 4: Place the tertiary aminated glass sheet (1-a) obtained in step 3 in a reactor, control the temperature at 5-10° C., slowly add 5 g of an acetone solution of 40% 5-chloromethyl salicylaldehyde by mass percentage onto the surface of the glass sheet, take it out after 2 hours, and use acetone to wash and remove the unreacted 5-chloromethyl salicylaldehyde on the glass sheet. After drying, obtain a surface quaternized glass sheet (1-a).

[0034] Step 5: Add 6.3 g of N,N-dimethylbenzylamine on the surface of the quaternized glass sheet (1-a), react at 90°C for 12 hours, then take it out, rinse the glass surface with ethanol and deionized water in turn, and vacuum dry it to obtain a surface-grafted quaternary ammonium cation and phenol ammonium zwitterion glass sheet (1-a), the structure of which is shown in the following formula:

[0035]

[0036] Surface grafted quaternary ammonium cations and ammonium phenol zwitterionic glass sheets (1-a)

[0037] The glass substrate, the hydroxylated glass sheet (1-a) obtained in step one, and the glass sheet (1-a) with quaternary ammonium cations and phenolic ammonium zwitterions grafted on the surface were cut into 3*0.5 cm glass strips respectively, placed in anhydrous ethanol, and soaked for 2 hours. Then, infrared spectroscopy was performed. There was a medium-intensity absorption peak at 1694 nm, which is a typical characteristic peak of aromatic aldehyde carbonyl C=O. The glass substrate and the hydroxylated glass sheet (1-a) obtained in step one did not have this peak, thereby confirming that the quaternary ammonium cations and phenolic ammonium zwitterions had been successfully grafted on the surface of the glass sheet (1-a).

[0038] Example 2 Preparation of glass sheet (1-b) grafted with quaternary ammonium cations and phenol ammonium zwitterions on the surface

[0039] According to the method and operation steps of Example 1, the N,N-dimethylbenzylamine in step 5 of Example 1 is replaced with N,N-dimethyldodecylamine, and a glass sheet with quaternary ammonium cations and phenol ammonium zwitterions grafted on the surface is obtained in the same manner, as shown in formula (1-b):

[0040]

[0041] Surface grafted quaternary ammonium cations and phenolic ammonium zwitterionic glass sheets (1-b).

[0042] Example 3 Preparation of glass sheet (1-c) grafted with quaternary ammonium cations and phenol ammonium zwitterions on the surface

[0043] According to the method and operation steps of Example 1, the N,N-dimethylbenzylamine in step 5 of Example 1 is replaced with pyridine to obtain a glass sheet (1-c) with quaternary ammonium cations and phenol ammonium zwitterions grafted on the surface. The structure thereof is shown in the following formula:

[0044]

[0045] Surface grafted quaternary ammonium cations and phenolic ammonium zwitterionic glass sheets (1-c).

[0046] Example 4 Preparation of glass sheet (1-d) grafted with quaternary ammonium cations and phenol ammonium zwitterions on the surface

[0047] According to the method and operation steps of Example 1, the N,N-dimethylbenzylamine in step 5 of Example 1 is replaced with an ethanol solution of N,N-dimethylethanolamine with a mass percentage concentration of 50%, to obtain a glass sheet (1-d) with quaternary ammonium cations and phenol ammonium zwitterions grafted on the surface. The structure of the glass sheet is shown in the following formula:

[0048]

[0049] Surface grafted quaternary ammonium cations and phenolic ammonium zwitterionic glass sheets (1-d).

[0050] Example 5 Characteristics of glass sheets with surface grafted quaternary ammonium cations and phenolic ammonium zwitterions

[0051] According to GB / T 24368-2009 Detection of hydrophobic contaminants on glass surfaces. Contact angle measurement method, the pure water contact angles of the glass sheets of Examples 1 to 4, the hydroxylated glass sheets, and the glass sheets with quaternary ammonium cations and phenol ammonium zwitterions grafted on the surfaces were measured. See Table 1.

[0052] Table 1 Pure water contact angle of glass slide

[0053] Sample No. 1-a 1-b 1-c 1-d Glass substrate Hydroxylated glass Water contact angle θ 8.8 12.3 5.5 0 52.5 41.7

[0054] The test results in Table 1 show that the water contact angle of the glass substrate decreases after hydroxylation treatment; after quaternary ammonium cations and phenolic ammonium zwitterions are grafted onto its surface, the water contact angle decreases more significantly, indicating that quaternary ammonium cations and phenolic ammonium zwitterions have been successfully grafted onto the surface of the glass sheet, and that the surface of the glass sheet has super hydrophilicity. When applied to the field of glass packaging, the glass surface has the application characteristics of anti-fog, anti-fouling, and rainwater self-cleaning.

Claims

1. A method for grafting quaternary ammonium cations and phenol ammonium zwitterions onto glass surfaces, characterized in that The steps include: Step 1: Add a mixed solution of 98% concentrated sulfuric acid and 30% hydrogen peroxide on one side of a cleaned and dried glass substrate, control the temperature at 20-120° C. for 0.5-50 hours, then take out the glass substrate, clean the surface of the glass sheet with deionized water, and then vacuum dry at 60-90° C. to obtain a surface hydroxylated glass sheet; The volume ratio of concentrated sulfuric acid to hydrogen peroxide in the mixed solution is 9:1 to 6:4, and the amount of the mixed solution is 2 to 200% of the mass of the glass substrate; Step 2: Add an aminosilane coupling agent solution to the surface of the hydroxylated glass sheet obtained in step 1, place the glass sheet in an oven at 30 to 130° C., and take it out and cool it after controlling the time for 0.5 to 20 hours to obtain a glass sheet with a surface amino group; The mass ratio of aminosilane coupling agent: ethanol: water in the aminosilane coupling agent solution is 1-5: 50-98: 1-48, and the amount of the aminosilane coupling agent solution is 2-200% of the mass of the glass substrate; Step 3, after the amination-treated glass sheet obtained in step 2 is placed in a reactor at 20-60° C., epichlorohydrin is slowly added to the surface of the amination-treated glass sheet, and the reaction time is controlled to be 0.5-20 hours, and then unreacted epichlorohydrin is blown away with N2 to obtain a glass sheet with tertiary amine groups on the surface; The amount of epichlorohydrin used is 5 to 500% of the mass of the glass substrate; Step 4: Add 5-chloromethyl salicylaldehyde solution to the surface of the tertiary-amined glass sheet obtained in step 3, put it into a reactor at 0-60° C., control the reaction time to 0.5-50 hours, then take it out and use acetone to wash and remove the unreacted 5-chloromethyl salicylaldehyde on the glass sheet, and after drying, obtain a surface quaternized glass sheet; The mass ratio of 5-chloromethyl salicylaldehyde to organic solvent in the 5-chloromethyl salicylaldehyde solution is 0.01 to 0.5:1, and the amount of the 5-chloromethyl salicylaldehyde solution is 2 to 200% of the mass of the glass substrate; Step 5, adding a tertiary amine solution to the surface of the quaternized glass sheet obtained in step 4, placing the glass sheet in a reactor at 20 to 90° C., controlling the reaction time to 0.5 to 50 hours, washing the glass surface with a solvent, recovering the unreacted tertiary amine, and drying the glass to obtain a glass with quaternary ammonium cations and phenol ammonium zwitterions grafted on the surface; The mass ratio of tertiary amine to solvent in the tertiary amine solution is 0.5:0-5, and the amount of the tertiary amine solution is 5-500% of the mass of the glass substrate; The tertiary amine has a structure shown in general formula (1) or general formula (2): Wherein R1, R2 and R3 in the general formula (1) are selected from substituted or substituted C1-C 18 Hydrocarbyl, wherein R in the general formula (2) is selected from -F, -Cl, -Br, -OH, (CH3)2N-, -COOH, -SO3H or substituted or unsubstituted C1-C 18 One or more hydrocarbon groups.

2. A method for grafting quaternary ammonium cations and phenolic ammonium zwitterions onto a glass surface according to claim 1, characterized in that The aminosilane coupling agent refers to one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-ethyl-3-aminopropyltrimethoxysilane, N-ethyl-3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane and 3-aminopropyldiethoxymethylsilane.

3. A method for grafting quaternary ammonium cations and phenolic ammonium zwitterions onto a glass surface according to claim 1, characterized in that The organic solvent refers to one or more of acetone, butanone, cyclohexanone, methyl acetate, ethyl acetate, chloroform, 1,2-dichloroethane, carbon tetrachloride, tetrahydrofuran, 1,4-dioxane, decahydronaphthalene, toluene, chlorobenzene, dimethyl sulfoxide or N,N-dimethylacetamide.

4. A method for grafting quaternary ammonium cations and phenolic ammonium zwitterions onto a glass surface according to claim 1, characterized in that The solvent refers to one or more of water, methanol, ethanol, acetone, butanone, cyclohexanone, methyl acetate, ethyl acetate, chloroform, 1,2-dichloroethane, carbon tetrachloride, tetrahydrofuran, 1,4-dioxane, decahydronaphthalene, toluene, chlorobenzene, dimethyl sulfoxide or N,N-dimethylacetamide.

Citation Information

Patent Citations

  • A method for grafting polymers onto glass surfaces

    CN102295418A

  • Method for preparing waterproof and antifogging surface modified glass

    CN103043919A

  • Symtriazine biochemical modified glass surface sensor, manufacturing method and application of sensor

    CN103940794A

  • Hollow glass micro-spheres surface modification method

    CN104130597A

  • A kind of method of glass surface graft polyammonium sulfonate inner salt

    CN104355549B

Cited By

  • Application of functionalized silane coupling agent in surface modification of bioactive glass

    CN117049794A

  • Application of a Functional Silane Coupling Agent in the Surface Modification of Bioactive Glass

    CN117049794B

  • Application of multifunctional silane coupling agent in surface modification of bioactive glass

    CN117069389A

  • Application of a Multifunctional Silane Coupling Agent in the Surface Modification of Bioactive Glass

    CN117069389B